2019
DOI: 10.4103/nmj.nmj_93_18
|View full text |Cite
|
Sign up to set email alerts
|

Towards 2030 target for hepatitis B and C viruses elimination: Assessing the validity of predonation rapid diagnostic tests versus enzyme-linked immunosorbent assay in state hospitals in Kaduna, Nigeria

Abstract: Introduction:Sub-Saharan Africa accounts for 25% of the estimated global 325 million people with chronic hepatitis B and C virus infections. Weak blood transfusion systems facilitate the spread of both hepatitis B and C virus infections. This is worsened by the absence of sustainable quality assurance programs and perennial shortage of sensitive screening kits. We aim to compare the validity of rapid diagnostic tests (RDTs) with the World Health Organization-recommended quality-assured enzyme-linked immunosorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…We also detected antibodies to the hepatitis C virus in 1.73% of the study population. Recent studies conducted in various parts of Nigeria reported hepatitis C sero-prevalence rates that ranged from 0.5% to 3.0%, with an average of 1.73% [ 28 29 30 31 ]. This perfect concordance is again evidence of the high quality and reliability of the NAIIS study.…”
Section: Discussionmentioning
confidence: 99%
“…We also detected antibodies to the hepatitis C virus in 1.73% of the study population. Recent studies conducted in various parts of Nigeria reported hepatitis C sero-prevalence rates that ranged from 0.5% to 3.0%, with an average of 1.73% [ 28 29 30 31 ]. This perfect concordance is again evidence of the high quality and reliability of the NAIIS study.…”
Section: Discussionmentioning
confidence: 99%
“…AUC was chosen as the evaluation method because it is more suitable for assessing the value of prediction performance using both balanced and unbalanced data sets [41]. Here is the formula for AUC as shown in (9).…”
Section: 𝑃𝑟𝑒𝑐𝑖𝑠𝑖𝑜𝑛 =mentioning
confidence: 99%
“…Although RDTs have advantages in speed and ease of use, they often have lower sensitivity and specificity compared to more sophisticated laboratory diagnostic methods. Therefore, RDT results usually require further confirmation using more accurate diagnostic procedures [9]. In addition to RDTs, detection can also be done with the help of artificial intelligence technologies, such as machine learning.…”
Section: Introductionmentioning
confidence: 99%